Increasing Farming Efficiency Through the Utilization of Cattle Livestock Waste for Composure as Community Income - Bagus Dimas Setiawan; Judo Laksono; Zulhapi Utama Adlan; Betty Herlina; Syintia Dwi Agustina (SATKRIYA : Jurnal Pengabdian Kepada Masyarakat, 2023)
Farm-scale input values are still a problem for the community, especially farmers, in providing fertilizers. The existence of livestock waste is one of the problems for breeders in Air Satan Village. The purpose of this service activity is to assist the Village community in increasing the value of farming efficiency by using cattle waste/manure to be processed into organic fertilizer as an additional source of income for the Village community. The method used in this service is counseling and training in making organic fertilizer for breeders in Air Satan Village. The results of this activity provide significant benefits for the people of Air Satan Village, who still need to familiarize themselves with the reuse of livestock waste into organic fertilizer, where the waste from cow manure is just thrown away without any further processing. The processing of this organic fertilizer is made faster by adding IMR as a bioactivator. The organic fertilizer produced can help improve soil fertility in Air Satan Village and its surroundings. Using organic fertilizers from livestock waste can increase the efficiency of fertilizers in farming so that they can be developed and used as a source of income for the community.